Analysis of reservoir parameters on the basis of well logging and DST of Miocene gas reservoirs in the central part of the Carpathian Foredeep, Poland - Maruta, Michał; Solecki, Marek L.; Chruszcz-Lipska, Katarzyna; Stachowicz, Katarzyna; Dubiel, Stanisław; Zubrzycki, Adam (Geologos, 2020)
In the Polish part of the Carpathian Foredeep, an intensification of gas exploration and exploitation from Miocene strata took place in the middle of the twentieth century. In spite of a good degree of geological and reservoir recognition, the area of the Carpathian Foredeep is still considered to be prospective for the discovery of new gas reservoirs. Here we analyse statistically selected reservoir parameters of Miocene deposits, such as total porosity, effective permeability and reservoir water inflow. These parameters have been determined on the basis of interpretations of results of well logs and reservoir tests with tubular bed samplers (DST, Drill Stem Test). Analytical results in the form of regression and dependence of the logarithm of permeability as a function of porosity show a weak correlation. However, in the study area, the distribution of porosity values for Miocene strata is close to normal.